265. SIGNIFICANCE OF AGR2 IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Konishi, Hirotaka; Takabatake, Kazuya; Kataoka, Satoshi; Shibamoto, Jun; Furuke, Hirotaka; Shiozaki, Atsushi; Fujiwara, Hitoshi; Otsuji, Eigo
Abstract: Anterior gradient 2 (AGR2) promotes tumor growth and make a worse prognosis in several cancers, especially in adenocarcinoma. However, comprehensive functional analysis of AGR2 in esophageal squamous cell carcinoma (ESCC) has not been reported. In the present study, the functional analysis and clinical significance of AGR2 were examined using ESCC cell lines and clinical samples. AGR2 was upregulated in ESCC cell lines and ESCC tissue sample. The downregulation of AGR2 suppressed cell proliferation and increased the proportion of G2/M-phase cells. Furthermore, phosphorylation of p53 in TP53-wild-type ESCC and osteosarcoma cells was also promoted. However, these changes were not observed in TP53-mutant ESCC cells. Immunohistochemistry results showed that high AGR2 and low p53 expression in ESCC tissue was correlated with a worse prognosis. These results suggest that although AGR2 enhances cell proliferation by inhibiting p53 phosphorylation in TP53-wild-type ESCC, the same mechanism does not regulate cell functions in TP53-mutant ESCC due to suppression of TP-53 function. In conclusion, AGR2 plays an important role in ESCC progression and might be a useful prognostic marker in patients with TP53-wild-type ESCC.